T. S. Eliot : no centenário do seu nascimento - Lima, José Luís Araújo (1989)
One hundred years after the birth of T. S. Eliot, the relevance of his achievement as a poet is firmly established and, as such, should be remembered. This is the author's point of departure for a brief analysis of certain tendencies of the eighties; he thereby foresees that a different evaluation of Eliot's poetry might occur in the future, not by putting in question the quality of his realization but by shifting the emphasis from some poems to others.